Pain: Peripheral and Central Sensitization - Ahmet Yılmaz,; Süreyya Ergin, (Archives of Rheumatology, 2006)
Various intracellular substances are secreted from macrophages, lymphocytes and mast cells in response to inflammatory process in damaged tissue. The nociceptive stimulus by itself may induce a neurogenic inflammatory response and cause secretion of substance P, neurokinin A, calcitonine gene related peptid. Secretion of these peptides stimulates the high threshold nociceptors thereby establishing peripheral sensitization. The events that occur in the periphery after trauma induce peripheric sensitization and primary hyperalgesia. Any mechanical stimulation which is painless normally may induce pain sensation (allodynia). These changes after trauma are related to the events that occur in dorsal horn of spinal cord and called as central sensitization. (Rheumatism 2006; 21: 105-10)